Evaluation on Service Coverage of Jatiwekas Water Treatment Plant of Tulungagung Regency Water Supply Company - Inka Muthia Ardhana; Taty Alfiah; Yonik Meilawati Yustiani (Department of Environmental Engineering - Universitas Pasundan - Indonesia, 2022)
Water Supply Company (WSC) of Tulungagung Regency uses treated water from the Jatiwekas WTP for distribution. Water Treatment Installation (WTI) Jatiwekas has three processing units, i.e., WTP with a capacity of 50 L/s (WTP 1), WTP with a capacity of 100 L/s (WTP 2), and WTP with a capacity of 40 L/s (WTP 3). The Jatiwekas WTP consists of flocculation, sedimentation, filtration, and reservoir. The objective of this study is to evaluate the WTP and calculate water demand by considering 90% service coverage. The research was conducted by field observations to obtain information. Based on SNI 6773:2008, most of the Jatiwekas WTP has met the requirements of the package type WTP, except for WTP 3 which has not met because its capacity exceeds the design of the WTP package unit, which only has a discharge rate of 1-50 L/s while the capacity of WTP 3 reaches 100 L /s. The Jatiwekas WTP does not meet the design criteria of the Directorate General of Public Works of Republic Indonesia, which states that the service coverage for small towns with a population of 20,000– 100,000 is 90%, to achieve 90% service coverage, the Jatiwekas WTP needs to increase water production capacity by 123.9 L/s.